Relationships between changes in self-reported physical activity, sedentary behaviour and health during the coronavirus (COVID-19) pandemic in France and Switzerland. Issue 6 (19th March 2021) - Cheval, Boris; Sivaramakrishnan, Hamsini; Maltagliati, Silvio; Fessler, Layan; Forestier, Cyril; Sarrazin, Philippe; Orsholits, Dan; Chalabaev, Aïna; Sander, David; Ntoumanis, Nikos; Boisgontier, Matthieu P.
ABSTRACT: To assess whether changes in physical activity and sedentary behaviour during the COVID-19 lockdown are associated with changes in mental and physical health. Observational longitudinal study. Participants living in France or Switzerland responded to online questionnaires measuring physical activity, physical and mental health, anxiety, and depressive symptoms. Paired sample t-tests were used to assess differences in physical activity and sedentary behaviour before and during lockdown. Multiple linear regressions were used to investigate associations between changes in physical activity and changes in mental and physical health during lockdown. 267 (wave1) and 110 participants (wave2; 2 weeks later) were recruited. Lockdown resulted in higher time spent in walking and moderate physical activity (~10min/day) and in sedentary behaviour (~75min/day), compared to pre COVID-19. Increased physical activity during leisure time from week 2 to week 4 of lockdown was associated with improved physical health (β=.24, p =.002). Additionally, an increase in sedentary behaviour during leisure time was associated with poorer physical health (β=−.35, p =.002), mental health (β=−.25, p =.003), and subjective vitality (β=−.30, p =.004). Ensuring sufficient levels of physical activity and reducing sedentary time can play a vital role in helping people to cope with a major stressful event, such as the COVID-19 pandemic.